Дослідження особливостей використання систем накопичення енергії при роботі трейдерів на енергоринку України - Довгалюк, Оксана Миколаївна; Саїдов, Шералі Нуралійович; Яковенко, Іван Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Виконаний аналіз основних систем накопичення електричної енергії, які можуть використовуватися трейдерами для підвищення ефективності роботи на ринку електричної енергії в Україні. Розглянуто основні технічні характеристики та особливості функціонування різних видів систем накопичення енергії в умовах ринку електричної енергії України. Розроблено критерій економічної ефективності використання систем накопичення енергії для роботи трейдерів, який враховує поточну ситуацію на ринку електричної енергії, технічні характеристики систем накопичення та особливості функціонування конкретного трейдера. З використанням запропонованого критерію визначено найбільш ефективні системи накопичення енергії для роботи трейдерів в умовах нового лібералізованого ринку електричної енергії в Україні.

The analysis of the energy storage systems role in the electric power systems operation in modern conditions of energy storage technologies development and the introduction of the electricity market in Ukraine performed. The energy storage systems classification by energy storage type, which is based on the World Energy Council general approach, has been reviewed. The analysis of the main technical characteristics and functioning features of energy storage systems various types that can be used by traders to improve the work efficiency in the conditions of the Ukraine electric energy market has been performed. The traders work features in the conditions of reforming the Ukraine electric energy market identified. Based on these features, the possibility of increasing the traders' work efficiency when using energy storage systems is revealed. The economic efficiency criterion in the energy storage systems using for the traders work, which takes into account the current situation on the electric energy market, the energy storage systems technical characteristics and the particular trader operating characteristics, has been developed. The using traders possibility comparison of various energy storage systems when working on the Ukraine electric energy market has been carried out. The most effective energy storage systems for the traders work in the new liberalized Ukraine electric energy market are determined using the proposed technical and economic criterion.
Peculiarities investigation of the using energy accumulation systems at the traders work on the energy market of Ukraine
Keywords: акумулювання; система накопичення; електрична енергія; стиснене повітря; accumulation; energy storage systems; electric energy; compressed air